2012
DOI: 10.1111/j.1574-6968.2012.02573.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of wide host range lytic bacteriophage AP22 infecting Acinetobacter baumannii

Abstract: Acinetobacter baumannii plays a significant role in infecting patients admitted to hospitals. Many A. baumannii infections, including ventilation-associated pneumonia, wound, and bloodstream infections, are common for intensive care and burn units. The ability of the microorganism to acquire resistance to many antibiotics, disinfectants, and dehydration assures its long-term survival in hospital settings. The application of bacteriophages is a potential tool to control A. baumannii infections. Bacteriophage AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 20 publications
6
50
0
Order By: Relevance
“…Bacteriophage ØABP-02 and ØABP-04 were classified into the family Myoviridae. This family was also reported in bacteriophages ABp53, ZZ1 and AP22 [16,18,19].…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Bacteriophage ØABP-02 and ØABP-04 were classified into the family Myoviridae. This family was also reported in bacteriophages ABp53, ZZ1 and AP22 [16,18,19].…”
Section: Resultsmentioning
confidence: 92%
“…To date, most of A. baumannii bacteriophage isolates are DNA phages [14,15,16,18,19,22]. PFGE analysis revealed that phage DNA ØABP-01 and ØABP-04 have genome sizes of approximately 30 kb and ØABP-02 showed a larger genome size of approximately 240 kb (Fig.…”
Section: Phage Nucleic Acid Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…EU418428). Nevertheless, the host ranges of the Pseudomonas and Acinetobacter bacteriophages were remarkable compared with those of other species-specific bacteriophages (Merabishvili et al, 2009;Popova et al, 2012). The overall morphology, genomic characterization and hostrange results suggested that these bacteriophages are very good candidates for BT.…”
Section: Discussionmentioning
confidence: 90%